Peculiarities and Efficiency of Collaborative Learning in Educational Process - Usmanova Nilufar (Researchparks Publishing, 2022)
In recent years, a number of new theories have emerged that consider the learner as the center of the educational system. These ideas originate from the concepts of situational learning, collaborative learning and constructivist approaches to learning, they were also fundamental to the new model of the economy based on knowledge. The article deals with the issues based on analyzing peculiarities and efficiency of collaborative learning in educational process.